THE NECESSITY AND EFFECTIVENESS OF DISTANCE LEARNING - Vergolyas, Maya; Verholias, Olexander; Vergolyas, Oleksandr (Sworld-Us Conference proceedings, 2025)
Independent work plays a key role in the process of distance education, ensuring effective assimilation of knowledge and formation of necessary skills. In the absence of direct contact with teachers, it is independent activity that becomes the main way to